(untitled) (CIPEEX, 2024)
IN THE CURRENT SOFTWARE DEVELOPMENT SCENARIO, THE INCESSANT SEARCH FOR HIGH QUALITY AND EFFICIENCY IS A PRESSING NEED. THE INCREASING COMPLEXITY OF APPLICATIONS, ALONG WITH THE PRESSURE TO PERFORM RAPID RELEASES AND OTHER INHERENT CHALLENGES, OFTEN MAKE THE REQUIREMENTS GATHERING PROCESS A SIGNIFICANT OBSTACLE, HARMING THE FINAL QUALITY OF THE SOFTWARE. IN THIS CHALLENGING CONTEXT, THE PRESENT RESEARCH, BASED ON A COMPREHENSIVE LITERATURE REVIEW, HAS THE PRIMARY OBJECTIVE OF DEEPENING THE UNDERSTANDING OF BEST PRACTICES RELATED TO REQUIREMENTS ELICITATION. OBTAINING VALUABLE INSIGHTS INTO HOW TO EXTRACT AND DEFINE REQUIREMENTS EFFECTIVELY IS CRITICAL TO ENSURING EFFICIENT DELIVERY OF SOFTWARE PROJECTS UNDER DEVELOPMENT. THIS IMPROVEMENT WILL ENABLE THE SOFTWARE TO MEET STAKEHOLDER EXPECTATIONS WITH GREATER PRECISION AND SATISFACTION, PLAYING A CRUCIAL ROLE IN THE SUCCESS AND EXCELLENCE OF DELIVERING HIGH-QUALITY DIGITAL SOLUTIONS. THEREFORE, THIS RESEARCH AIMS TO CONTRIBUTE SIGNIFICANTLY TO THE IMPROVEMENT OF REQUIREMENTS ELICITATION PRACTICES IN THE CONTEXT OF SOFTWARE DEVELOPMENT, PROMOTING EXCELLENCE AND INNOVATION IN THE TECHNOLOGY INDUSTRY, WITH THE VISION OF CONTINUALLY IMPROVING THE ABILITY OF ORGANIZATIONS TO OFFER DIGITAL SOLUTIONS THAT MEET CONSTANTLY EVOLVING DEMANDS.